HADRAH ACCOUNTING: AN ETHNOGRAPHIC APPROACH TOWARDS PEOPLE IN BERU, LAMONGAN - Fikriya Hanim Kardiya Emaluta; Sasongko Budisusetyo; Tjiptohadi Sawarjuwono (UNIB Press, 2020)
This study aims at describing and defining accounting practices of hadrah community located in Beru Lamongan, in order to find out the reconstruction of the accounting concept towards the hadrah community that is rich in local cultural values. Hadrah, which is also known as ishari or ishari organization, is a sacred performing art accompanied by radad dance moves and tambourines. Hadrah performances will be held only if requested for celebrations, Qur'an recitation events, and marriages. In an ishari organization, knowledge of accounting for financial records and statements is certainly needed for the survival and existence of hadrah organization. This research uses an ethnographic approach. Data were obtained from informants, members of hadrah group in Beru, through participative observation, in-depth interviews with informants and documentation. The results showed that the payment obtained was only as a means to preserve and ensure the existence of the Hadrah community in Beru, Lamongan. The reconstruction of the accounting concept in hadrah community, who are also members of ishari organizations, particularly in Beru, shows that accounting is seen as an activity of recording income and expenditure that prioritizing the value of honesty and responsibility.